KNOWLEDGE AND SELF-REPORTED PREPAREDNESS OF FINAL YEAR DENTAL STUDENTS REGARDING MEDICAL EMERGENCIES DURING DENTAL PROCEDURES â€“ A MULTI-CENTER STUDY - Farid, Huma; Yasir, Ayesha; Ali, Syeda Khizra; Hamayun, Shanza; Khan, Shanzay; Zahid, Syeda Nayab (Pakistan Oral & Dental Journal, 2023)
A dental student competent in recognizing and managing medical emergencies will have a safe practice in the future. The objective of this study was to assess the knowledge and self-reported preparedness of senior dental students regarding medical emergencies during dental procedures.This cross-sectional study was conducted among final-year dental students in all dental teaching hospitals of Rawalpindi and Islamabad in Pakistan. All final-year students enrolled for the session 2021 in dental colleges of two cities were included in this research study (n=350). A closed-ended questionnaire was used for the data collection procedure consisting of questions related to self-assessed medical emergency preparedness and participantsâ€™ knowledge/competency regarding specific medical emergencies. A scoring system was used for rating the responses of the participants. Demographic variables were expressed in frequencies and percentages. Comparisons between responses of male and female students regarding self-assessed medical emergency preparedness and knowledge of specific medical emergencies/procedures were made using Pearsonâ€™s chi-square test of association. Point Biserial test was used to determine a correlation between knowledge score and responses to self-assessed medical emergency preparedness (scale variable vs. dichotomous nominal variable). Association/ correlation was considered statistically significant with a P value â‰¤0.05.Out of 325 students, 204 participated with a response rate of 62.7%. The mean age of the students was 22.89(Â±1.108) years. Female and male students constituted 76% (n=155) and 24% (n=49) respectively. Half of the respondents (103, 50.5%) scored â€œgoodâ€ in self-assessed medical emergency preparedness. The majority of the male students scored â€œgoodâ€ as compared to female students (65.3% vs. 45.8%)with a statistically significant association(p=0.20). Most of the students (128, 68.7%) scored â€œfairâ€ when asked about specific medical emergencies. Respondents with high knowledge scores tend to; inquire about medical history, obtain filled health history forms, had knowledge about emergency drugs/their routes of administration, and administer intramuscular injection with a weak positive statistically significant correlation (pâ‰¤0.05).The scores regarding self-reported preparedness and knowledge of undergraduate students towards medical emergencies in our study were mediocre and demanded more emphasis on educating and reinforcing medical emergency skills and knowledge at the undergraduate level.
Keywords: Medical Emergencies; Dental Students; Knowledge; Self-reported preparedness; Dental Education